PERANCANGAN WEBSITE RUMAH MAKAN NINIK SEBAGAI MEDIA PROMOSI MENGGUNAKAN UNIFIED MODELLING LANGUAGE - Suharni -; Eel Susilowati; Fahrial Pakusadewa (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
In some restaurants that are often found, generally these restaurants ony provides food menu information written on the menu list. Besides that, buyers must come to find out the menu list of food being sold today. The website has enormous benefits as a medium of information. Buyers can get information about the food menu in restaurants that already have websites without having to come. Restaurant owners also do not need to provide information abour menu availability if a buyer comes. To describes in analyzing a system from a website that will be made and can be communicated with system professionals and ptogrammers, it is necessary to design a model of the system. The model that will be used for making Ninik restaurant website is UML (Unified Modelling Language). The design diagram on the model is Usecase Diagram, Activity Diagram and Class Diagram. An overview of the appearance of each website page can be made wih the Input/Output ( I/O) interface design. Based on the result of the system design that has been made, it can be implemented by system develovers into website that can be used by the public and especially buyers as a means of information media regarding the food menu available at Ninik’s restaurant.